Pelatihan Komunikasi Efektif Pada Lansia Bagi Kader Posyandu - Yeni Devita (Jurnal Pengabdian UntukMu NegeRI, 2024)
Posyandu cadres are the main driving pillars in health development. The knowledge and skills of cadres are needed and need to be improved in order to carry out their cadre roles well. This community service aims to improve the knowledge and skills of elderly Posyandu cadres in communicating effectively with the elderly when performing their duties. This training was conducted in the Sidomulyo Inpatient Health Center area of Pekanbaru Riau with 8 participants. The instrument used to measure knowledge uses a questionnaire consisting of 10 questions. The knowledge of cadres is measured before and after training. The results of the training measurement found an increase in the average knowledge of cadres before and after training by 2.88 points. The average knowledge before training was 5.87 and the average knowledge after training was 8.75. The results of this community service show that training can improve knowledge and skills. The Puskesmas should be able to provide other training for Puskesmas cadres